Quinoxalines in Oral Health: From Antimicrobials to Biomaterials - Montana, Marc; Vanelle, Patrice (Mini Reviews in Medicinal Chemistry, 2025)
Quinoxalines are a versatile class of nitrogen-containing heterocyclic compounds that have been extensively studied for their diverse pharmacological properties. Recently, interest has grown in exploring quinoxaline derivatives for applications in oral health, driven by their unique mechanisms of action and potential to address major challenges in dental medicine. This review comprehensively examines the recent progress in the development of quinoxaline-based compounds targeting oral pathogens responsible for dental caries, periodontitis, and other biofilm-associated diseases. Beyond their antimicrobial effects, quinoxalines also exhibit anti-inflammatory properties by modulating key molecular pathways implicated in periodontal inflammation, thereby offering a dual therapeutic potential. Moreover, their incorporation as functional additives in restorative dental materials is emerging, aiming to enhance antimicrobial efficacy and improve material performance. Despite promising in vitro and in vivo data, several critical barriers must be overcome before clinical translation can be realized. These include ensuring biocompatibility with oral tissues, achieving formulation stability under the dynamic conditions within the oral environment, and optimizing delivery systems to ensure targeted, sustained release at the site of action. This review highlights current strategies to address these challenges and proposes directions for future research, including advanced formulation technologies and comprehensive preclinical evaluations. Ultimately, quinoxaline derivatives hold significant promise as multifunctional agents capable of integrating antimicrobial, anti-inflammatory, and biomaterial-enhancing properties to improve oral health outcomes. This synthesis of current knowledge supports continued investigation into quinoxalines as novel therapeutics and functional components for dental care.
Keywords: biomaterial